The Reaction of the Underground Press to the Displacement of Polish Children from the Zamość Region to Siedlce in 1943 - Kozaczyńska, Beata (City and War, 2022)
During World War II, the Germans committed many crimes against Poles, whom they forcibly displaced from the Zamość region. After the Poles had been driven out of their homes, they were placed in transit camps, which included the German transit camp in Zamość (UWZ-Lager Zamosc). In the Zamość camp, the Germans conducted racial tests and separated children from their mothers. After a few days or several weeks, children who were “racially worthless” (and therefore unfit for Germanization) were transported under severe freezing conditions in crowded cattle carriages, without water or food. The Germans sent six “death transports” from Zamość to a town in the eastern part of the Warsaw district. One of these transports carrying children and old people displaced from the Zamość region reached the train station in Siedlce. Many of the children were in disastrous health. The inhabitants of Siedlce and the surrounding area rushed to help, organizing a quick action to save the lives and health of the children. This work is the result of research project No. 2017/25/B/HS3/01085, funded by the National Science Centre in Kraków.